2014
DOI: 10.5430/jnep.v4n5p159
|View full text |Cite
|
Sign up to set email alerts
|

Meanings, beliefs and attitudes of the neonatal unit staff in México about the parents' participation in a neonatal unit: A qualitative approach

Abstract: Background and context: The two most important factors and determinants of morbidity and mortality of the newborn are prematurity and low birth weight, children are admitted in neonatal unit and require many specialized therapeutic interventions, thus, a medical and technical focus is predominating. The staff of neonatal unit has a challenge in provide support to parents´ participation in the care of their child. The study was performed in a public hospital offering second-level care in San Luis Potosí, México… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…A study in Mexico, found that fathers perceived the NICU staff to favour mothers, as they allowed them more easy access to breastfeed or deliver expressed milk. [20] The fathers perceived they had little importance and were considered a source of infection, though they did have an essential role in communicating with NICU staff and transmitting that information to the mother. [20] Rwandan fathers could benefit from more intentional respect and inclusion in the NICU, and participate in the infant care when they are able to be present in the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Mexico, found that fathers perceived the NICU staff to favour mothers, as they allowed them more easy access to breastfeed or deliver expressed milk. [20] The fathers perceived they had little importance and were considered a source of infection, though they did have an essential role in communicating with NICU staff and transmitting that information to the mother. [20] Rwandan fathers could benefit from more intentional respect and inclusion in the NICU, and participate in the infant care when they are able to be present in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…[18] The Poppy Project in Wales emphasised the need for NICU parents to have a good rapport and active support with the NICU nursing staff. [19] Individual support from staff has been shown to decrease parental stress, anxiety and depression, [20] which gives parents more opportunities to learn about their new infant and provide care.…”
Section: Introductionmentioning
confidence: 99%
“…Aspectos éticos basados en la Ley General de Salud, 7 aprobación del Comité Local de Ética e Investigación en Salud del Hospital del Niño y la Mujer, con el registro HNM/03-2015/023 y consentimiento informado de las participantes.…”
Section: Instrumentos a Cuestionario Picker´s Pediatric Acute Careunclassified